Medieval Islamic Medicine - Daniel Martin Varisco (International Institute of Islamic Thought, 2008)
One of the acknowledged contributions to late medieval western education was the tradition of Islamic medicine, both for its role in preserving earlier Greek medical knowledge and, as the authors of this book demonstrate, for innovative and creative advances in medical diagnosis, treatment, and patient care. Pormann and Savage-Smith provide an informative overview of the history of medicine in the Islamic world, from the Prophet’s sayings to the period of extensive contact with European colonialism. Their work supplements and updates the slim volume ofManfred Ullmann, to whom this book is dedicated, entitled Islamic Medicine (Edinburgh University Press: 1976). Consciously avoiding a sweeping history of a vast scientific field, the authors narrate a readable story of Islamicmedicine and provide suggestions for further reading at the end of each chapter. Without question, this volume can be considered the best and most critical introduction to the field and a guide for future research. One of the most important critical issues probed is the impact of Greek medicine, especially as mediated through Byzantine sources, on the emergence of a distinctive “Islamic” approach to medicine. The synthetic corpus of the Hippocratic writings and the works of Galen formed the holistic basis for the scientific development of medical theory (chapter 2), including the humoral system, diet, pharmacology, disease diagnosis, anatomy, and surgery. The authors also discuss other currents of medical knowledge, from the Alexandrian medical curriculum to the knowledge found in Sasanid Persia, Syriac Christian sources, India, and even unto China. The translation of non- Arabic texts was a major contribution, but “Greek medicine as well as some elements of other medical traditions were transformed and not merely given permanent right of abode as aliens, they were assimilated, adapted, and finally adopted in the truest sense of the word into Islamic society” (p. 37) ...